Comparison of Stress and Strain Distribution Patterns in Canine Implant and Maxillary Bone in Three Occlusal Schemes Using Finite Element Analysis - Fathi, Amirhossein; Hoshyar, Younes; Ebadian, Behnaz; Ghorbani, Mahsa (European Journal of Dentistry, 2024)
Objectives This study aimed to compare the pattern of stress and strain distribution in canine implant and maxillary bone in the anterior group function (AGF), posterior group function (PGF), and canine guidance (CG) occlusal schemes by finite element analysis (FEA).Material and Methods In this in vitro experimental study, a dental implant (10 × 4.1 mm) was inserted at the site of the maxillary canine in a model of the maxilla in Mimics software. The implant was scanned three-dimensionally and the data were transferred to SolidWorks software. The von Mises stress, shear stress, deformation, and strain were calculated in the AGF, PGF, and CG occlusal schemes by FEA.Statistical Analysis Data were analyzed by ABAQUS software to calculate the stress transferred to the canine implant and maxillary bone in the three occlusal schemes.Results The maximum and minimum von Mises stress, elastic strain, shear stress, and deformation were noted in the AGF and PGF occlusal schemes, respectively, in all teeth.Conclusion The PGF showed minimum von Mises stress, elastic strain, shear stress, and deformation in the canine implant and maxillary bone. Thus, it appears than the PGF is the best occlusal scheme for maxillary canine implant followed by the CG scheme.
Keywords: dental occlusion; dental implants; single tooth; finite element analysis